EL BRÓCOLI AMARGO - Houtart, Francois (2024)
Broccoli cultivation is growing in Ecuador as an export crop. This economic sector generates approximately 5000 direct and 15000 indirect job posts, an important addition to the country's labor market. lt is clear that this production is inscribed within the project of transforming the basis of an economy that depends on the extractive sector, seeking to "implement cutting edge technology in agriculture so as to position the country as the first [producer of theworld" (cita!!). However, we need to ask about the social and ecological price that such production entail. Most broccoli production takes place in the form of large enterprise based on monocropping, which has shown to have negative effects for the environment as well as for communities.